Excavation Deformation Analysis of Foundation Pits and Its Influence on Surrounding Buildings - CHENG Xinyu; FU Chenghua; LIU Jian; JIANG Linjie (Renmin Zhujiang)
With the efficient use of urban space,the construction of new foundation pit projects is becoming more and more difficult,and the research on the excavation deformation of foundation pits and its impact on surrounding buildings is becoming more important.Taking a deep foundation pit project as an example,this study uses a three-dimensional finite element model to numerically simulate the actual excavation process.Moreover,the deformation characteristic of foundation pits and its influence on the surrounding buildings are comprehensively analyzed with the measured deformation data.The results reveal that during the excavation of a new foundation pit,the overall lateral displacement of the retaining structure toward the inside of the foundation pit occurs,and the maximum displacement occurs in the middle of the foundation pit retaining piles adjacent to the side of the buildings.The settlement of soil around and at the bottom of the foundation pit is “groove-shaped”,namely that when the excavation goes deeper,the settlement is greater.The excavation of the new foundation pit leads to the different uniform settlement of surrounding buildings,but with the construction of the retaining structure,the deformation of buildings decreases gradually and tends to be stable.The research results can provide some theoretical reference for the design and construction of similar deep foundation pit projects.